VALUE CHAIN ANALYSIS OF COFFEE IN ENHANCING THE COMPETITIVENESS OF INDONESIA’S COFFEE AGRIBUSINESS - Saidul Alam (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to analyze the structure of the coffee value chain and its role in enhancing the competitiveness of Indonesia’s coffee agribusiness. The research employed a qualitative descriptive approach using a case study method in several major coffee-producing regions in Indonesia, including Aceh, North Sumatra, and Sulawesi. Data were collected through in-depth interviews, field observations, and document analysis involving coffee farmers, processing actors, traders, SMEs, and coffee exporters. The data were analyzed thematically to describe the value chain structure and identify key factors influencing agribusiness competitiveness. The results indicate that Indonesia’s coffee value chain consists of five main stages: production, post-harvest handling, processing, distribution, and marketing. The highest value added is generated at the processing and marketing stages, while farmers at the upstream level receive relatively low value added. Key factors influencing coffee agribusiness competitiveness include product quality, technology adoption, institutional roles, and access to capital. Optimizing the value chain through improved post-harvest quality, technological adoption, and strengthened institutional support can enhance the competitiveness of Indonesian coffee in the global market. This study recommends improving access to finance and strengthening farmers’ capacity as key strategies for developing a sustainable national coffee agribusiness.